2017
DOI: 10.15171/ijb.1585
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-Mediated Transformation of the Oryza sativa Thaumatin-Like Protein to Canola (R Line Hyola308) for Enhancing Resistance to Sclerotinia sclerotiorum

Abstract: Background:Canola is an agro-economically oilseed crop. Yield loss due to fungal disease of stem rot caused by Sclerotinia sclerotiorum is a serious problem in canola cultivation. Thaumatin-like proteins are large groups of the pathogenesis-related proteins which provide resistance to the fungal infection in response to invading pathogens and play a key role in plant defense system. Objectives: Transformation of the rice tlp into canola via Agrobacterium-mediated transformation and evaluation of the antifungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…As shown in Figure 8b, PR1 and PR5 were induced by cold acclimation and cold shock. Overexpression of a rice PR5 gene in rapeseed enhanced the resistance to Sclerotinia sclerotiorum , a fungal pathogen that caused Sclerotinia stem rot in rapeseed (Aghazadeh et al 2017). We propose that overexpression of PR genes in rapeseed might produce rapeseed germplasm with tolerance to cold and S. sclerotiorum .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 8b, PR1 and PR5 were induced by cold acclimation and cold shock. Overexpression of a rice PR5 gene in rapeseed enhanced the resistance to Sclerotinia sclerotiorum , a fungal pathogen that caused Sclerotinia stem rot in rapeseed (Aghazadeh et al 2017). We propose that overexpression of PR genes in rapeseed might produce rapeseed germplasm with tolerance to cold and S. sclerotiorum .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that both Pru-TLP from cherry and Mal-TLP from apple exhibit a reasonably high endo-β-1,3-glucanase activity [29]. TLP proteins extracted from the leaves of multiple transgenic rice plants have been shown to possess a wide range of β-1,3-glucanase activities [32]. In this work, four recombinant PlTLPs were found to have β-1,3-glucanase activity, and the optimal reaction pH of these recombinant PlTLPs was determined to be 4.…”
Section: Discussionmentioning
confidence: 99%
“…TLP proteins can bind and degrade β-1,3-glucan, which is the main component of the fungal cell wall [30], laying the foundation for TLP proteins to further damage the fungal cell membrane [31]. For instance, a rice TLP protein with glucanase activity showed a significant inhibitory effect on the growth of Sclerotinia sclerotiorum and could change the permeability of the hyphal membrane [32]. Furthermore, many TLP proteins with antifungal activity can penetrate the fungal cell membrane and increase the content of reactive oxygen species (ROS) in the cell, leading to oxidative damage [18,33].…”
Section: Introductionmentioning
confidence: 99%
“…An increase of up to 15-fold in glyphosate herbicide use in cultivation compared to 1974 [ 166 ] was recorded, contributed by the rapid spread of RR crops globally [ 156 , 160 ]. Overreliance on a few HT crops and single active herbicidal ingredients has caused leaking of HT traits [ 160 , 167 , 168 , 169 ], with cases relating to all of the introduced HT systems being reported worldwide [ 170 ].…”
Section: Breeding For Economically Important Agronomic Traits Of mentioning
confidence: 99%